Fundamentals of Entrepreneurship (ENT 300) : Business plan of Danity's cafe / Brandon Beckham Siali Benjamin … [et al.] - Siali, Brandon Beckham; Abang Hasyim, Dayang Hasmiera Azreen; Larry, Nazel Isaac; Hazali, Nur Iffahanis (2019)
Danity's offers coffees with custom-made coffee beans that are imported from Indonesia, with milkshakes with several flavours, some brownies, waffles and also cakes. These will give a high satisfaction for the costumers. The Danity's cafe is managed by 4 managers and 2 part timers. Overall, it consists of 6 workers.